Revision of the genus Regulaneuria (Ephemeroptera, Heptageniidae,Ecdyonurinae), with description of a new species - Mu, Pengxu; Huang, Xiaolei (Zootaxa, 2023)
Regulaneuria Zhou, a genus of Ecdyonurinae endemic to China, is revised. Regulaneuria chongchongae sp. nov., a new species from Hainan Island of southern China, is described and illustrated at all stage. The differentiated characters that distinguish Regulaneuria from its closely related genus Asionurus are also clarified.